Strategi Guru PAI dalam Pembelajaran Hadits di SMAN 1 Teladan Yogyakarta - Sri Anugrah Indriani; Suyadi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
This study aims to describe the learning process of Hadith included in PAI (Islamic education) learning of SMAN 1 Teladan Yogyakarta. Moreover, it also aims to explain the factors influencing its learning process as well as the strategy used by the teacher to help the students in understanding some hadith. This study belongs to qualitative research and uses interview as well as observation in getting the data. The research result shows that the learninng process of hadith is carried out by reading some hadith for the tenth graders, memorizing some hadith for the students of eleventh graders, and explaining the meaning of hadith for the students of twelfth graders. In its learning process, it was found that there are some factors influencing students’ understanding both from the teacher as well as the students. The strategies used by the teacher in the learning process include reviewing hadith delivered by the students, making a list of hadith, and asking the students to mentioning the sanad of hadith